Evaluation of salt stress and molecular analysis of genetic variation of Iraqi rice cultivars - Amar Mandal; Arshad Alhasnawi; Haider Jasim; Azhar Mohamad (Society for Indonesian Biodiversity, 2019)
Abstract. Mandal AM, Alhasnawi AN, Jasim H, Mohamad A. 2019. Evaluation of salt stress and molecular analysis of genetic variation of Iraqi rice cultivars. Biodiversitas 20: 3309-3314. The salinity-stress casts an inhibitory effect on rice, which is not only complex but also a key reason for impeding plant growth as well as decreasing crop productivity. A helpful method to improve our understanding in this space would be to make a direct comparison pertaining to the response to salinity by considering two closely related cultivars, i.e. Yassimen and Anber-33, which demonstrate varying levels of salt-tolerance. Exposing rice seeds to high concentrations of 200mM NaCl stress resulted in considerable impact on shoot, chlorophyll content and root growth. The growth of both cultivars was considerably decreased due to salt toxicity. A range of differences was seen in terms of growth parameters due to interaction between cultivars and salt levels. It can be said that the various cultivars vary in terms of their salt tolerance with regards to seedling growth and seed germination. Based on the results from the Inter-simple sequence repeats (ISSR) data, cultivar-Anber-33 had 27 bands in total, while for cultivar-Yassimen, it was 25. These results demonstrated that ISSR markers proved to be a valuable method for determining genetic variation, fingerprinting, classification, and identification of Iraqi rice cultivars.